2016
DOI: 10.1002/adsc.201501049
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Three‐Component Reaction of 3‐(Tri‐n‐ butylstannyl)allyl Acetates, Aldehydes, and Triorganoboranes: An Alternative to the Carbonyl Allylation Using α,γ‐Substituted Allylic Tin Reagents

Abstract: The reaction tolerates 1‐aryl as well as 1‐hetaryl substituted 3‐(tri‐n‐butylstannyl)allyl acetates, aryl, hetaryl, alkenyl as well as alkyl aldehydes and various boranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…To overcome such limitations, we reported that catalytically generated allylic heterobimetallic species such as allylic Pd/boryl and Pd/stannyl species are useful intermediates for the umpolung allylation of aldehydes to provide ( Z )- and ( E )-homoallylic alcohols, respectively, with good to high stereoselectivity . However, such methods require the independent preparation of different starting materials.…”
mentioning
confidence: 99%
“…To overcome such limitations, we reported that catalytically generated allylic heterobimetallic species such as allylic Pd/boryl and Pd/stannyl species are useful intermediates for the umpolung allylation of aldehydes to provide ( Z )- and ( E )-homoallylic alcohols, respectively, with good to high stereoselectivity . However, such methods require the independent preparation of different starting materials.…”
mentioning
confidence: 99%
“…The three-component reaction of B(pin)-substituted allyl acetates, aldehydes, and triorganoboranes proceeded successfully (Scheme 18). [40] This method was compatible with various aldehydes, which could be problematic in the metal-catalyzed allylation reaction of aldehydes. For example, 4-and 2-hydroxybenzaldehydes were used without prior protection of the hydroxyl group.…”
Section: Diastereoselective Synthesis Of Homoaldol Equivalent Productsmentioning
confidence: 97%
“…Moderate diastereoselectivities were also observed for heteroaryl substrates. Previous studies of Horino and co-workers had also demonstrated the formation of (Z)-anti-homoallylic alcohol, but in this case, using 3-(pinacolatoboryl) allyl acetates, aldehydes, and triorganoboranes under the influence of a Pd-PCyPh 2 catalyst system (Horino, Sugata & Abe, 2016).…”
Section: Scheme XII Reaction System For the Synthesis Of Allylic Alcmentioning
confidence: 81%
“…2016 has also been a productive year in the field as yet another study for the facile process of (E)-antihomoallylic alcohol production was developed using a palladium-xantphos-catalyzed reaction system of 3-(tri-n-butylstannyl)allyl acetates, aldehydes, and triorganoboranes (Scheme XI) (Horino, Sugata & Abe, 2016). This served as alternative to the typical carbonyl allylation bound with the limitation of introducing n-alkyl, sec-alkyl, and aryl groups, which came from triorganoboranes, into the alkene.…”
Section: Scheme XII Reaction System For the Synthesis Of Allylic Alcmentioning
confidence: 99%